Eficacia del sulfato ferroso y multimicronutrientes en el incremento de hemoglobina en los niños de 6 a 36 meses de edad, en los distritos de San Juan de Rontoy y Llamellín, provincia Antonio Raimondi, Ancash - Becerril Grandez, Neisi (2019)
Objective: To determine the efficacy of ferrous sulfate and multimicronutrient in increasing hemoglobin in children6 to 36 months of age, in the districts of San Juan de Llamellín and Rontoy in Antonio Raimondi province, Ancash.Material and Methods: Using the pre experimental design, we selected a total of 100 children, 55 Llamellín district,of which 50.9% were women and 49.1% men. District of San Juan de Rontoy were selected 45 children, 55.6%were female and 44.4% male. In both districts, children with moderate or severe anemia, ferran supplement received1 mg / kg / day, while children with mild anemia or without anemia received supplemental multimicronutrient 1packet daily, known as “sprinkles”. Results: At the beginning of the program to 3.6% had severe anemia, 50.9%moderate anemia, mild anemia 16.4% and 29.1% were free of anemia, bone, that overall 70.9% of children wereanemic Llamellín. In the district of San Juan de Rontoy, 6.7% had severe anemia, 26.7% moderate anemia, mildanemia 33.3% and 33.3% without anemia, therefore, 66.7% have some degree of anemia. During the intervention,the mean hemoglobin among children who received ferran Llamellín was increased from 8.1 to 10.7 g / dl (p<0.05). Also in the district of San Juan de Rontoy mean hemoglobin increased from 8.9 to 10.7 g / dl (p <0.05).While multimicronutrient administration in the district resulted Llamellín, increased hemoglobin discrete 11.0 to11.3 g / dl (p> 0.05). Also in the district of San Juan de Rontoy increased slightly from 11.1 to 11.6 g / dl (p> 0.05).Conclusion: The administration of ferran in children Llamellín districts and San Juan de Rontoy in supplement formis effective in reversing iron deficiency anemia in children 6–36 months of age (p <0.05).